ACOUSTICAL PROBLEMS AND REQUIREMENTS IN OPEN PLANNED OFFICES- ELEVATIONS ON A CASE STUDY - Acar, Baris; Yugruk Akdag, Nese (YILDIZ TECHNICAL UNIV, FAC ARCHITECTURE, 2008)
The open-plan offices are extensive spaces designed to accommodate a large number of office workers. An open-plan office can work reasonably well when carefully designed, especially in terms of noise. In an open-plan office, full-height partitions aren't used; therefore spreading noises caused by conservation, office machines ect., can be disturbing. In order to provide good acoustical conditions in an open plan office, adequate speech privacy, speech intelligibility and acceptable background noise level have to be obtained. In this study, it has been intended to investigate the precautions that should be taken to provide acoustic comfort conditions, during the design of the open planned office places which have been in common use also in our country nowadays. For this aim, acoustic measurements were performed in an open planned office placed in Kartal-Istanbul. The office is digitally modeled by using the software Odeon 8.0 which performs the exact acoustic calculations with the impressions of radial analysis. The acoustic comfort conditions has been analyzed in different sound absorption properties and separator heights by the Odeon 8.0 software. In conclusion, the relation between separator properties and required sound absorption values of open planned offices' inner surfaces are explained by some concrete values.
Keywords: Open planned office; acoustic comfort; acoustic design; Architecture